Comparison of Superficial Surgical Site Infection in Simple Interrupted and Hybrid Mattress Suture after Posterior Approach for Spine Surgery - Ajid Risdianto; Rully Hanafi Dahlan; Achmad Adam; Firman Priguna; Muhammad Zafrullah Arifin (Faculty of Medicine Universitas Padjadjaran, 2015)
Objective: To compare the incidences of superficial surgical site infection after posterior approach procedures in simple interrupted suture groups compared with hybrid mattress suture group. Methods: A number of 38 patients who underwent posterior approach procedure were randomized into two groups. First group was sutured using simple interrupted suture while the second was using hybrid mattress suture. Bivariate statistical analysis was performed using Chi square test and Mann Whitney test. The superficial surgical site infection incidence was evaluated and recorded for both groups.Results: A superficial surgical site infection was found in 26.3% of the simple interrupted group and no infection was found in the hybrid mattress group. Statistical analysis showed a p value of 0.046.Conclusions: Compared to simple interrupted suture, hybrid mattress suture has less superficial surgical site infection in posterior approach for spine surgery.Keywords: Hybrid mattress suture, simple interrupted suture, superficial surgical site infection, wound healing DOI: 10.15850/ijihs.v3n2.589